Comparison of The Effectiveness of Active Recovery and Cold-Water Immersion on Fatigue Recovery in Recreational Runners - Marcella Febry Utami; Agus Rusdiana; Tian Kurniawan (Journal of Physical Education Health and Sport, 2025)
This study examines the effectiveness of Active Recovery (AR) and Cold-Water Immersion (CWI) in reducing blood lactate as an indicator of fatigue recovery in recreational runners after completing a 5-kilometer run. Using a pretest–posttest crossover design, seven recreational runners participated in two recovery conditions AR and CWI with a one-day washout period between treatments. Lactate levels were measured before and after each recovery session. The analysis showed that AR lowered lactate levels from 8.286 mmol/L to 6.257 mmol/L (p = 0.106), while CWI reduced levels from 5.243 mmol/L to 3.300 mmol/L (p = 0.057). While neither method showed statistically significant differences, CWI revealed a more noticeable trend in accelerating lactate reduction toward OBLA values compared to AR. These findings indicate that CWI could provide faster metabolic recovery for recreational runners needing shorter recovery periods, whereas AR remains appropriate for gentler recovery focused on sustaining movement ease. Due to the limited sample size, additional studies with a larger population are advised to provide stronger support for these recovery strategies.